2010
DOI: 10.1007/s00170-009-2398-8
|View full text |Cite
|
Sign up to set email alerts
|

Powder injection molding 440C stainless steel

Abstract: In this work, the processing steps for producing 440C stainless steel parts by means of powder injection molding technique were investigated. The molded specimens were debinded by solvent debinding followed by thermal debinding methods and were sintered under vacuum atmosphere. Effective densification took place in the temperature range 1,230-1,240°C in the sintering. After heat treatment, specimens sintered at 1,240°C for 30 min had the tensile strength of 876.3 MPa, the hardness of 57.7 HRC. Pitting mainly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…In this batch (FS3) the carbon content is higher due to the higher percentage of PP in this feedstock, which resulted in larger grain size. Unlike in FS2 sample, where the higher carbon content resulted in higher pore content than in FS1, in FS3 sample, residual carbon has led to less porosity and higher density due to the local melting effect, which has been reported in many studies [29,30]. In these studies, it has been reported that an increase in carbon content results in an increase in local melting regions.…”
Section: Resultsmentioning
confidence: 88%
“…In this batch (FS3) the carbon content is higher due to the higher percentage of PP in this feedstock, which resulted in larger grain size. Unlike in FS2 sample, where the higher carbon content resulted in higher pore content than in FS1, in FS3 sample, residual carbon has led to less porosity and higher density due to the local melting effect, which has been reported in many studies [29,30]. In these studies, it has been reported that an increase in carbon content results in an increase in local melting regions.…”
Section: Resultsmentioning
confidence: 88%
“…The debinding process can be used for this purpose; thus, some binder left in the brown part can provide extra carbon content during sintering. 38 All these negative effects can be enhanced due to the presence of carbon. In this respect, carbon should be avoided in PH stainless steels; Nb is used to grab the carbon and form Nb carbides, thereby preventing the carbon from interfering in the precipitate hardening process.…”
Section: Sintering Aspectsmentioning
confidence: 99%
“…In this study martensitic 440C stainless steel is used as a feedstock in MIM, although the extensive shrinkage and formation of carbide networks during sintering limit its commercial potential [28,29]. As far as the authors know, the corrosion protection of porous stainless-steel parts has not been widely reported.…”
Section: Introductionmentioning
confidence: 99%